Search Engines as a New Type of Stakeholder of Contemporary Organizations - Wielki, Janusz (Advanced Information Technologies for Management – AITM 2008, 2008)
This paper deals with the problem of the impact of search engines on the functioning of contemporary organizations. In the first part an overview of the situation connected with the growing role of search engines in the business environment of contemporary organizations and the consequences of this process is briefly provided. The second part is focused on an analysis of the two basic forms of influence of search engines on contemporary organizations: direct and indirect. Finally the most significant conclusions and suggestions are provided.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 35, s. 168-176